Requirement for cobalamin by Salmonella enterica serovars Typhimurium, Pullorum, Gallinarum and Enteritidis during infection in chickens - Paiva, Jacqueline Boldrin de [UNESP]; Penha Filho, Rafael Antonio Casarin [UNESP]; Berchieri Junior, Angelo [UNESP]; Lemos, Manoel Victor Franco [UNESP] (Sociedade Brasileira de Microbiologia, 2011)
Salmonella enterica serovar Typhimurium synthesizes cobalamin (vitamin B12) only during anaerobiosis. Two percent of the S. Typhimurium genome is devoted to the synthesis and uptake of vitamin B12 and to B12-dependent reactions. To understand the requirement for cobalamin synthesis better, we constructed mutants of Salmonella serovars Enteritidis and Pullorum that are double-defective in cobalamin biosynthesis (ΔcobSΔcbiA). We compared the virulence of these mutants to that of their respective wild type strains and found no impairment in their ability to cause disease in chickens. We then assessed B12 production in these mutants and their respective wild type strains, as well as in S. Typhimurium ΔcobSΔcbiA, Salmonella Gallinarum ΔcobSΔcbiA, and their respective wild type strains. None of the mutants was able to produce detectable B12. B12 was detectable in S. Enteritidis, S. Pullorum and S. Typhimurium wild type strains but not in S. Gallinarum. In conclusion, the production of vitamin B12 in vitro differed across the tested Salmonella serotypes and the deletion of the cbiA and cobS genes resulted in different levels of alteration in the host parasite interaction according to Salmonella serotype tested.
Keywords: Salmonella; Cobalamin; gene deletion; Chickens